2011
DOI: 10.1136/oem.2011.064709
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis in occupational health: a comparison of intervention scenarios for occupational asthma and rhinitis among bakery workers

Abstract: Objectives Use of cost-benefit analysis in occupational health increases insight into the intervention strategy that maximises the cost-benefit ratio. This study presents a methodological framework identifying the most important elements of a cost-benefit analysis for occupational health settings. One of the main aims of the methodology is to evaluate cost-benefit ratios for different stakeholders (employers, employees and society). The developed methodology was applied to two intervention strategies focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…A generic national or regional price weight was used in 13 studies (19%), 9 (13%) used a worker-specific weight, 3 (4%) the industry or company average, and 1 (1%) a job average with age differentiation. Variations -such as using the mean annual salary per staff member in the NHSL (47), the study group average (75, 100), or the national average (41, 45,48,56,60,62,64,(66)(67)(68)(69)(70)72,(83)(84)(85)87,89,93,95,97,99,103,107,(118)(119)(120)(121)(122)(123)(124) 47,63,65,74,(77)(78)(79)81,82,87,(100)(101)(102)108,109,112,114,117,(126)(127)(128) (48, 52, 53, 58, 65-67, 69,...…”
Section: Valuing Time Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small scale of most stores and cost considerations, the dough processing operation is still manual, which has long caused musculoskeletal disorders in employees. Most studies on the health of bakery workers have mostly focused on industrial bakeries in high-income countries, with emphasis on the effects of flour dust on the respiratory system [12][13][14]) or the allergies and skin problems it causes [14,15]. Forcier et al, compared musculoskeletal pain in workers among 7 departments of supermarkets in Canada and found that bakers were the second most likely to experience pain among all groups [13].…”
Section: Introductionmentioning
confidence: 99%
“…This would more closely align epidemiology with the risk characterization phase of risk assessment in which costs and benefits of risk management interventions are weighted and risks are appraised quantitatively (Phillips 2001). Alternative outcomes analysis, an example of a technique that can provide important insights in distinguishing association from causation, could be more routinely applied in assessing causal inference and attributable risk estimation (Jager et al 1990; Meijster et al 2011a, 2011b; Thomsen et al 2006). Alternative outcomes analysis allows for the conceptualization of causation in terms of causes of meaningful versus ignorable consequences, assuming these can be readily differentiated into one of these two options.…”
Section: Exposure Assessmentmentioning
confidence: 99%